Variations at multiple genes improve interleukin 28B genotype predictive capacity for response to therapy against hepatitis C infection - Neukam, Karin (2013)
To identify genetic factors that predict sustained virological response (SVR) to pegylated interferon (Peg-IFN)/ribavirin (RBV) in HIV/hepatitis C virus (HCV) genotype 1 or 4-coinfected patients and that enhance the predictive capacity of IL28B genotype in this population.